A Zambian Town in Colonial Zimbabwe: The 1964 "Wangi Kolia" Strike. (December 2015) - Phimister, Ian; Tembo, Alfred
Abstract: In March 1964 the entire African labour force at Wankie Colliery, "Wangi Kolia", in Southern Rhodesia went on strike. Situated about eighty miles south-east of the Victoria Falls on the Zambezi River, central Africa's only large coalmine played a pivotal role in the region's political economy. Described by Drum, the famous South African magazine, as a "bitter underpaid place", the colliery's black labour force was largely drawn from outside colonial Zimbabwe. While some workers came from Angola, Tanganyika (Tanzania), and Nyasaland (Malawi), the great majority were from Northern Rhodesia (Zambia). Less than one-quarter came from Southern Rhodesia (Zimbabwe) itself. Although poor-quality food rations in lieu of wages played an important role in precipitating female-led industrial action, it also occurred against a backdrop of intense struggle against exploitation over an extended period of time. As significant was the fact that it happened within a context of regional instability and sweeping political changes, with the independence of Zambia already impending. This late colonial conjuncture sheds light on the region's entangled dynamics of gender, race, and class.